Environmental impact assessment in Brazil: a case study of the Belo Monte hydroelectric facility licensing process - Brocca Caballero, Cassia; Moreira Siqueira, Tirzah (Revista Brasileira de Desenvolvimento Regional, 2024)
The Environmental Impact Assessment (EIA) is a process that consists in the identification, prediction and evaluation of the impacts of human activities that have potential to cause significant impacts on the environment. It analyses whether certain activities have a high potential for degradation and impact, in order to judge whether or not such activities can be implemented and, if they are, mitigate or compensate their negative impacts. Therefore, the aim of this study was to analyze the applied methods on the environmental licensing of Belo Monte Hydroelectric Facility through qualitative research, investigating the Environmental Impacts Study (EIS) of this project and its impacts on the local population. Furthermore, the fulfilment of the licensing agency requirements and its posture in face of the unredeemed requirements has also been assessed. It was inferred that many of the terms that were required by the licensing agency to prove the project environmental feasibility were not accomplished, and few were just partially attended. Keywords: Belo Monte Hydroelectric Facility; environmental impact assessment; environmental licensing; environmental impact study.